Gelfand Triples and Their Hecke Algebras Harmonic Analysis for Multiplicity-Free Induced Representations of Finite Groups /: Harmonic Analysis for Multiplicity-Free Induced Representations of Finite Groups. (2020) - Scarabotti, Fabio; Tolli, Filippo
No abstract available